Perception on Malaysia Fundmyhome Crowdfunding Initiative for Affordable Housing - Khairul Adlee, Nurul Faziera; Misiran, Masnita; Md Yusof, Zahayu; Sapiri, Hasimah; Amit, Norani (2022)
Crowdfunding is based on a relationship where funders invest certain amount of funds in a project and expecting returns. Its non-conventional relationship lies in the type of funders, in which crowdfunding platform is utilizing massive participation from general public to become the funder, rather than using a standard one channel platform for loan acquisition purposes. In Malaysia, this platform is being innovated into real estate crowdfunding initiative, tabled in the Budget 2019, to ease current restriction of home ownership among category of people that is otherwise difficult to secure mortgages from conventional platform. Therefore, this paper investigates the perception of Malaysian young adults towards property crowdfunding platform using Exploratory Factor Analysis. The aim is to determine the perceptions of the targeted group towards this investment vehicle. Results showed that four factors influence Malaysian perception toward property crowdfunding among young adults. The highlighted factors are risk tolerancy, return expectations, saving expectations and financial knowledge. This initiative has potential to become the driver for sustainable development, as the risk of faults in paying mortgage can be reduced significantly compared to traditional means